1989
DOI: 10.1159/000276484
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on 25 Years of Piagetian Cognitive Developmental Psychology, 1963–1988

Abstract: In this article some of the issues are examined that have arisen in one quarter of a century of intensive research on cognitive development from a Piagetian perspective. It is suggested that there is no evidence clearly confirming the existence of Piaget’s cognitive structures in explicit form. Consequently, neo-Piagetian theories have proliferated, in an attempt to conceptualize the increasingly powerful cognitive systems that have been observed to develop with age. Research on the object concept indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 58 publications
(85 reference statements)
1
37
0
1
Order By: Relevance
“…Empirical evidence appears to support Piaget's basic descriptions of the stages of cognitive development (Elkind & Flavell, 1969;Halford, 1989aHalford, , 1989bNeimark, 1975Neimark, , 1979Pascual-Leone, 1989b;Sigel & Hooper, 1968). For example, Elkind and Flavell (1969) and Sigel and Hooper (1968), reported on replication studies of Piaget's work that confirmed the occurrence of most of the phenomena he reported.…”
Section: Empirical Support For Piaget's Cognitive Stagesmentioning
confidence: 76%
See 2 more Smart Citations
“…Empirical evidence appears to support Piaget's basic descriptions of the stages of cognitive development (Elkind & Flavell, 1969;Halford, 1989aHalford, , 1989bNeimark, 1975Neimark, , 1979Pascual-Leone, 1989b;Sigel & Hooper, 1968). For example, Elkind and Flavell (1969) and Sigel and Hooper (1968), reported on replication studies of Piaget's work that confirmed the occurrence of most of the phenomena he reported.…”
Section: Empirical Support For Piaget's Cognitive Stagesmentioning
confidence: 76%
“…For example, Elkind and Flavell (1969) and Sigel and Hooper (1968), reported on replication studies of Piaget's work that confirmed the occurrence of most of the phenomena he reported. Similarly, Halford (1989a), in reflecting on 25 years of Piaget's work, found that Piaget's empirical work has held up reasonably well and Neimark (1975) concluded that the earlier findings of Piaget appear to be clearly replicable and that his stages of development provide an accurate description of a vast amount of data.…”
Section: Empirical Support For Piaget's Cognitive Stagesmentioning
confidence: 97%
See 1 more Smart Citation
“…As Halford (1989) points out even within cognitive psychology there are competing theories of cognitive development and Zohar and Aharon-Kravetsky (2005) argue that whilst the promotion of cognitive conflict is a significant instructional method there is still inconclusive evidence regarding the effectiveness of this strategy.…”
Section: Applicability Of Piaget's Theory and Some Critiquesmentioning
confidence: 99%
“…são generalizáveis (Battro, 1978). Entretanto, dando que, segundo a teoria de Piaget, somente pode ser aprendido o que for assimilável a uma estrutura pré-existente, pode-se razoavelmente concluir que o conceito piagetiano de estruturas seja uma antecipação da atual teoria de esquemas, de que trata o presente trabalho (Halford, 1989; Pascual-Leone, 19891. Por outro lado, em psicologia também se emprega o termo esquema quando se trata de representação mental ou imagem simplificada de um objeto.…”
unclassified